On the Peculiarities of Terminological Word Group with Meaning “Value-Based Pricing” and the Problem of Their Equivalence in Translation - Rolak, Irene (Respectus Philologicus, 2014)
The paper presents a semantic analysis of a range of selected terms along with contrastive characteristics of their syntagmatic and paradigmatic peculiarities. “Price”, “cost” and “value” are the basic notions of market economy and, correspondingly, the lexemes denoting them. As a result, the paper focuses on the information these lexemes transmit along with their equivalents in the Polish and Russian languages. Probable variants of their translation are also shown. The problem of evaluation of their linguistic volume refers to the functioning of these words in economic discourse as general notions (hyperonyms) that involve a range of particular ones. The author takes into consideration the factors, which have the impact on translation of the Polish and Russian terminological phrases (word groups) that are often calques of English terms. An adequate translation is influenced by the following: understanding of terminological and non-terminological nature of a phrase being translated, acquaintance with idiomatic expressions used at translation of English terminological lexis, taking into account the regularities of syntagmatic collocation of a word. On the basis of use of phrases from the Russian and Polish economic discourses, the author shows the characteristics of use for selected terms and gives some adequate variants of their translation. The analysis of relations within the terminological group under study has shown that in the process of translation and choice for synonyms terminological and non-terminological meaning of a word, use of idiomatic expressions in both target languages that are calques from English, a tradition in realization of syntagmatic collocation of a word should be taken into consideration.